Revisit intention and tourist orientation: a sustainable tourism development framework for natural and built attractions - Mardiatul Jannah; Mirandha Ariesca Riana; St. Aisyah (Jurnal Pariwisata Pesona, 2024)
This study aims to determine the direction of sustainable tourism development models for natural and artificial tourist attractions in South Sulawesi, focusing on tourist orientation and their interest in revisiting. The approach used is the quantitative Analytical Hierarchy Process (AHP) method and qualitative methods through surveys and interviews. A total of 145 tourist respondents were involved to measure their priorities in choosing tourist destinations. The research results show that tourists' orientation priorities are dominated by the desire to overcome boredom, followed by the search for new experiences, the need for healing, and knowledge. Natural tourism, particularly beaches and mountains in Bulukumba, Tana Toraja, Gowa, Maros, and Pangkep, is the respondents' top choice. Additionally, tourist attractions are the main factor influencing tourists' interest in revisiting, followed by service quality, facilities, and accessibility. This study recommends that destination managers focus more on developing sustainable natural tourism and improving services and facilities to attract tourists' revisits.